The Marxist Concept of Scientific Ideology - Meškauskas, Eugenijus (Problemos, 1978)
The article deals with the relation between the Marxist concept of scientific ideology and Marxist criticism of the ideological views typical of a class society, on the one hand, and with the methodological peculiarities of the scientific theory of socialism, on the other. Marxism interprets scientific ideology as an ideology of a new kind as regards its methodology and social role. The article also deals with the dependence of tie peculiarities of ideological development on the process of the appearance and subsequent disappearance of the objective prerequisites for the alienation in social relations.